The Level of Aspiration of Arab women Women’s Role in the Social Development “Algerian women as a model “ - Ala, Aicha (Social Empowerment Journal, 2019)
The thesis objective to verified of the Level of Aspiration and the role of women in social development, and to identify differences in the role of women in social development according to the variable levels of ambition and social situation. The research sample consisted of 240 women. To achieve the research objectives, Social development was verified the validity and stability of the tool, descriptive was adopted, resulted the study at the following results: - The level of Aspiration level is high through.- There aren’t statistically significant differences at a level of (α ≤ 0.01) between the dimensions of women’s role in social development.- There aren’t statistically significant differences at a level of (α ≤ 0.01) in mean grades the role of women in social development According a variables (levels of ambition and social situation).